Multiple Breath Washout for Early Assessment of Pulmonary Complications in Patients With Primary Antibody Deficiencies: An Observational Study in Pediatric Age - Secchi, Teresa; Baselli, Lucia Augusta; Russo, Maria Chiara; Borzani, Irene Maria; Carta, Federica; Lopopolo, Maria Amalia; Foà, Michaela; La Vecchia, Adriano; Agostoni, Carlo; Agosti, Massimo; Dellepiane, Rosa Maria (Frontiers in Pediatrics, 2022)
Background. In Primary Antibody Deficiencies (PADs), pulmonary complications are the main cause of morbidity, despite immunoglobulin substitutive therapy, antibiotic treatment of exacerbations and respiratory physiotherapy. Italian current recommendations for surveillance of PADs respiratory complications include the annual assessment of spirometry and the execution of chest High Resolution Computed Tomography (HRCT) every four years. Objective. This study aims to evaluate the effectiveness of Lung Clearance Index (LCI) as early marker of lung damage in patients with PADs. LCI is measured by Multiple Breath Wash-out, a non-invasive and highly specific test widely used in Cystic Fibrosis patients. Methods. Pediatric patients with PADs (n=17, 10, M, 7, F, age range 5-15 years) underwent baseline assessment of lung involvement with chest HRCT, Spirometry and Multiple Breath nitrogen Wash-out. Among them, 13 patients were followed up to repeat HRCT after four years, while performing Pulmonary Function Tests annually. Their baseline and follow-up LCI and FEV1 values were compared, taking HRCT as gold standard, using logistic regression analysis. Results. LCI (OR 2.3 [CI 0.1 – 52] at baseline, OR 3.9 [CI 0.2 -191] at follow-up) has a stronger discriminating power between altered and normal HRCT rather than FEV1 (OR 0.6 [CI 0.2 – 2] at baseline, OR 1.6 [CI 0.1 - 13.6] at follow-up). Conclusion. Within the context of limited sample size, LCI seems to be more predictive of HRCT alterations than FEV1 and more sensitive than HRCT in detecting non-uniform ventilation, in absence of bronchiectasis. A study of a larger cohort of pediatric patients followed longitudinally in adulthood is needed to challenge these findings.